(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
This research includes a Comsol Mutiphysics model describing the temperature distribution on aluminum during the laser conductivity welding process. The influence of laser power and speed on the welding process is discussed and compared with experiments. Numerical simulations of laser welding process have been performed to determine the temperature fields of laser impact to samples of aluminum. Numerical calculations are made for fiber laser. The plots of the temperature dependence on the surface and in the depth of aluminum samples on the velocity are analyzed for several power densities for this laser.